The Influence of Product Quality and Service Quality on Consumer Satisfaction and Purchising Decisions - Mulkan Ritonga; Rahma Muti’ah (International Journal of Integrated Science and Technology, 2023)
This research aims to see and determine the influence of product satisfaction and service quality on consumer satisfaction and purchasing decisions, both partially and simultaneously. The form of this research is quantitative descriptive research. Data and information collection uses a questionnaire as a research instrument. The population in this research is all consumers who purchased food or beverage products at the Bang Pendi Rantauprapat Cafe in the period June 2023 to August 2023, namely 540 people and the sample was determined using the Slovin formula with a margin of error of 5% so that the total sample was 277 buyers. Data analysis uses Structure Equation Version (SEM) with the help of the SmartPLS version 3 software program. The results of the research show that product quality (X1) has a good and broad influence on consumer satisfaction (Y) with a tcount value of 6.591 > ttable of 1.96 with percentage of 65.9%. Service quality (X2) has a positive and significant effect on customer satisfaction (Y) with a calculated t value of 2.603 > t table value of 1.96 with a percentage of 26.0%. Product quality (X1) has a good and partially large influence on purchasing choices (Z) with the price t statistic being higher than the t price table, namely 6.377 > 1.96 with a price percentage of 63.7%. Excellent service (X2) has a partially effective and large influence on purchasing decisions (Z) with t calculated being greater than t table, namely 5,168 > 1.96 with a percentage of 51.6%. Product quality (X1) and service quality (X2) simultaneously have a positive and significant effect on purchasing decisions (Z) through customer satisfaction (Y) with a t value greater than t table, namely 8.636 > 1.96 with a percentage of 86.30%.